2005
DOI: 10.1002/ceat.200500212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Approach for Process Development

Abstract: A novel method for process development is presented. The approach is based on the evaluation of available technologies and aiming at new and innovative designs by combining their best features in a creative way. The knowledge is extracted either directly from similar processes or from processes with sufficient analogy. A case study on melamine process development is given to illustrate the application of the methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The performance of the process is relied on the decisions made during process development" [1]. Especially for pharmaceutical products the downstream process accounts for a major part of the production costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the process is relied on the decisions made during process development" [1]. Especially for pharmaceutical products the downstream process accounts for a major part of the production costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Downstream process development is one of the most important stages of Active Pharmaceutical Ingredient (API) manufac-turing due to its crucial effect both on the lifecycle and performance of the final manufacturing process. 40 Moreover, downstream processing is the major contributor to the production costs of APIs. 41 Conventional API purification steps include recrystallization, precipitation, solvent extraction, distillation, chromatography, adsorbents and resins.…”
Section: The Role Of Osn In Downstream Processingmentioning
confidence: 99%
“…Therefore, systematic process development based on identification of justified optima is essential for efficient utilization of time and resources. Nfor et al (2009) identified four types of process synthesis strategies applicable to chemical industries: heuristics or knowledge-based strategies (Cziner et al, 2005), optimization-based strategies (Steimel et al, 2013;Grossmann and Daichendt, 1996), high-throughput experimentation strategies (Bhambure et al, 2011;Schuldt and Schembecker, 2013) and a combination of the aforementioned strategies (Ahamed et al, 2006). Each approach has strengths and weaknesses as discussed elsewhere (Nfor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual design or process synthesis in the early stage is thus viewed as the most important stage of process development (Cziner et al, 2005). Major decisions affecting the lifecycle of the process are made during development of the first process flowsheet.…”
Section: Introductionmentioning
confidence: 99%